Reflection of Racial Discrimination in “Freedom Writers” Film’s Dialogs - Azzahra, Aster Tania Nafiri; Hani, Umi (LPPM Universitas Bina Sarana Informatika, 2024)
This research aims to reflect on racial discrimination contained in the dialogue of Richard La Gravense's film Freedom Writers (2007). This film tells the story of a white teacher named Erin Gruwell who tries to resolve the racist conflict that occurred among her students at Woodrow Wilson High School in Long Beach, California. The film depicts how